Preventive control of postharvest gray mold in tomato by tautomycetin-producing Streptomyces sp. KRA20-350 - Ji Hye Choi; Huisoo Cho; Yugyeong Choi; Bomin Kim; Jae Woo Han; Hosung Jeon; Hokyoung Son; Young-Sook Kim; Gyung Ja Choi; Hun Kim (Postharvest Biology and Technology, 2027)

Comparative genomics and phenotypes of Listeria monocytogenes isolated from enoki mushrooms in South Korea and China - Wen Si Hu; So Hyeon An; Dong Woo Kim; Hyeong Uk Im; Seung Hun Lee; Yu Bao Li; Zi Xuan Liu; Zhi Wei Wang; A Ram Lee; Ui In Kim; Hyeon Ji Je; Yeon Ju Seo; et al. (Food Microbiology, 2026)

Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

Paraprobiotic Lacticaseibacillus paracasei HY7017 restores gut microbiota homeostasis and short-chain fatty acid production in cyclophosphamide-induced immunosuppressed mice - So Jeong Lim; Jae Yeon Joung; Ji Hun Jang; Jin Hwan Kim; Jiangyu Li; Nam Su Oh (Food Bioscience, 2026)

Applicability of conventional genotoxicity test guidelines to mRNA vaccines: a four-battery assessment of a SARS-CoV-2 mRNA vaccine candidate - Jae-Hun Ahn; Yun-Soon Kim; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Seo-Hyeon Bae; Jisun Lee; Jae-Hwan Nam; Byeong-Cheol Kang (Toxicological Research, 2026)
mRNA vaccine formulations are generally considered to pose a lower genotoxic risk than conventional small-molecule pharmaceuticals; however, long-term data regarding their potential genotoxicity remain limited. Furthermore, to date, no standardized genotoxicity testing guidelines specifically tailored to the unique characteristics of mRNA vaccines have been formally established. In this study, we conducted a comprehensive genotoxicity assessment of a SARS-CoV-2 Omicron variant mRNA vaccine candidate using a four-test battery, following a modified regimen that accounted for the unique characteristics of mRNA vaccines while adhering to OECD test guidelines: bacterial reverse mutation test (OECD TG 471), in vitro chromosomal aberration test (OECD TG 473), in vitro micronucleus test (OECD TG 487), and in vivo erythrocyte micronucleus test in mice (OECD TG 474). No significant genotoxic effects of the mRNA vaccine candidate were observed in any of the four assays. However, during the design and conduct of this study in accordance with existing genotoxicity guidelines, ambiguity arose as to whether test concentrations should be determined according to the mRNA component or the LNP component. In addition, we observed that, unlike the LNP administered alone, the mRNA vaccine candidate was associated with a reduction in the proportion of PCEs in the in vivo micronucleus assay. Although our mRNA vaccine candidate showed no significant evidence of genotoxicity, the experimental design and dosing regimen highlight the need to refine current regulatory testing guidelines for mRNA vaccines. We anticipate that our findings will contribute to the development of more appropriate genotoxicity guidelines for advanced therapy medicinal products (ATMPs), including mRNA vaccines.

Hybrid carbon framework of graphitic carbon and bamboo-like CNTs for stable lithium-metal anodes - SungJu Kim; Jae Hun Choi; Dae Soo Jung; Yun Chan Kang (Chemical Engineering Journal, 2026)

Nonclinical safety evaluation strategies for mRNA/LNPs platform agents: Evidence from comprehensive animal toxicity studies - Jae-Hun Ahn; Na-Young Lee; Hee-Jin Bae; Jooil Kim; Jina Kwak; Euna Kwon; Gahyun Roh; Seo-Hyeon Bae; Soo-Yeon Lee; Il Kwon Hwang; Jisun Lee; Hyo-Jung Park; et al. (Toxicology Letters, 2026)

Synergistic effects of seaweed powder and rheology modifiers on the reaction mechanism and pore architecture of geopolymer - Hyun-Soo Lee; Joo-Young Kim; Jae-Suk Ryou; Byeong-Hun Woo; Hong-Gi Kim (Journal of Cleaner Production, 2026)

Simultaneous bioelectricity generation and selective copper recovery via controlled two-step discharge strategy in a two-chamber microbial fuel cell using an unbuffered copper catholyte - Jun Hyun Kim; Hyeong Jae Kim; Dong Hun Lee; Sunghyun Kim (Bioresource Technology, 2026)

Sediment facies regulate organic and shell-derived carbonate carbon storage in the Shinan tidal flats, Korea - Yoon-Seo Kim; Yeo-Bin Park; Ji-Won Park; Eui-Joo Kim; Sang-Pil Lee; Seung-Jun Lee; Do-Hun Ryu; Ji-Su Ko; Jun-Mo Kim; Jae-Hoon Park; Yong-Sik Hong; Sang-Kyoung Lee; et al. (Regional Studies in Marine Science, 2026)

Polystyrene nanoplastic-encapsulated extracellular vesicles promote blood–brain barrier breakdown and accumulate in the brain - Min Jae Kim; Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Jae-Eon Lee; Hyeon-Gu Kang; DongJoo Joung; Eui-Man Jung; Beum-Soo An (Journal of Hazardous Materials, 2026)

Citrate-enabled process intensification reinforces energy and redox metabolism for sustainable bioproduction using Corynebacterium glutamicum - KwangYoung Park; Hoe-Suk Lee; Dong Young Lee; June-Ho Choi; Yunhee Jeong; SunJoo Park; Yunjeong Song; Jiyoung Park; Chan-Duck Jung; Hoyong Kim; Sung-Hyun Jo; Yun-Gon Kim; et al. (Bioresource Technology, 2026)

Weathered plastic particles negatively affect mouse primary neurons and glial cells - Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Yunsoo Chang; Min Jae Kim; DongJoo Joung; BuHyun Youn; Eun-Hee Lee; Eui-Man Jung (Archives of Toxicology, 2026)

Plant life form, biomass allocation, and belowground structure shape depth-dependent soil organic carbon accumulation as blue carbon sources in vegetated tidal flats - Jae-Hoon Park; Yeo-Bin Park; Ji-Won Park; Sang-Pil Lee; Do-Hun Ryu; Seung-Jun Lee; Jun-Mo Kim; Ji-Su Ko; Eui-Joo Kim; Yoon-Seo Kim; Young-Han You (Science of The Total Environment, 2026)

Oligomeric strategy for ether-free multiblock copolymer anion exchange membranes with ordered ionic channels for efficient alkaline water electrolysis - Jin Hyuk Kim; Eun Woo Lee; Hyuk Jin Roh; Jae Hun Lee; Jong Hak Kim (Chemical Engineering Journal, 2026)

Microbial markers of resilience and its correlation with reproductive performance in lactating sows under heat stress condition - Abdolreza Hosseindoust; Jun Young Mun; Sang Hun Ha; Habeeb Tajudeen; Priscilla Neves Silvestre; Jae Cheol Jang; Jin Soo Kim (Tropical Animal Health and Production, 2026)

Biological upcycling of conditionally biodegradable plastics: enzymatic depolymerization to microbial valorization and consolidated bioprocessing frameworks - Yunhee Jeong; Sol Min Han; Jieun Wu; KwangYoung Park; Yunjeong Song; Yung-Hun Yang; Kyung-Jin Kim; Jungoh Ahn; Kyungmoon Park; See-Hyoung Park; Si Jae Park; Eun Ju Yun; et al. (Systems Microbiology and Biomanufacturing, 2026)

Evolution and spread of H8Nx avian influenza viruses from wild birds in East Asia, 2019-2024 - Sae-hyeon Park; Sun-Hak Lee; Ye-Ram Seo; Dong-Ju Kim; Young-Jae Si; Hyesung Jeong; Suwoong Lee; Chang-Seon Song; Dong-Hun Lee (Archives of Virology, 2026)

Fatigue Behavior of 66 kV Wet-Type Submarine Cable for a Flexible Pull-In Installation System - Yun-Jae Kim; Dong-Suk Hong; Hyun-Kyung Kim; Yong-Hun Jung; Sung-Woong Choi (Journal of Marine Science and Engineering, 2026)
This work focuses on evaluating the fatigue characteristics of a 66 kV wet-type submarine cable. The analysis incorporates realistic offshore environmental conditions and considers installation through a flexible pull-in system. The target system was deployed at the Southwest Offshore Wind Farm in Korea, where the structural response of the cable is governed by combined wave- and wind-induced loading. To determine the ultimate limit state (ULS) behavior of the cable arranged in the flexible pull-in installation configuration, a global dynamic analysis was initially performed, from which time-dependent displacement histories were extracted under site-specific metocean conditions. The results indicate that lateral wave-induced loading dominates the global response owing to the vertically suspended configuration of the flexible pull-in installation system. A detailed local fatigue analysis was performed based on the critical loading scenarios identified from the global analysis. Prior to the fatigue evaluation, a numerical modeling approach for the local analysis of the 66 kV wet-type submarine cable was developed and validated through comparisons with experimental tensile test results. The developed numerical model successfully captured the axial stiffness characteristics and deformation response of the cable, demonstrating a discrepancy of less than 1% between the numerical predictions and experimental measurements. Fatigue analyses were performed for 120 displacement-based time-history loading cases derived from the global dynamic response. The results show that the fatigue damage is predominantly concentrated in the steel-wire armor, particularly near the fixed boundary region, identifying it as the governing fatigue-critical component. In addition, a parametric study of the wire-armor helix angle revealed that increasing the helix angle significantly improved the fatigue life by enhancing the bending flexibility and reducing the stress concentration under transverse loading. These findings provide practical insights into the fatigue-resistant design and optimization of wet-type submarine cables installed using flexible pull-in installation systems in floating offshore wind applications.

Exosomal microRNA profiling reveals candidate biomarkers and regulatory signatures associated with paratuberculosis disease status in goats - Eun-Yeong Bok; Tae Yoon Kim; Sang-Young Seo; Han-Gyu Lee; Young-Hun Jung; Seong Hwan Bae; Nam Su Oh; Tae Jin Cho; Hyeon Woo Park; Eui Cheol Shin; Jae Kyeom Kim (The Veterinary Journal, 2026)

Gaussian process-based data augmentable deep Bayesian neural network: Application to estimate the stress transfer length in pretensioned concrete beams - Byeong-Hun Woo; Dong-Hun Choi; Chan-Hyuk Park; Jee-Sang Kim; Jae-Suk Ryou; Kyung-Suk Yoo (Engineering Structures, 2026)

Erythropoietin-derived Non-erythropoietic Peptides Conferring Oxidative Stress Resistance to Keratinocytes and Fibroblasts - Min Ae Han; Janbolat Ashim; Youngheum Ji; Eunho Kang; Minchan Jeong; Sung Jae Kim; Wookyung Yu; Jin Hae Kim; Cheil Moon; Chang-Hun Lee (Cell Biochemistry and Biophysics, 2026)

Integrated MEA for polymer electrolyte membrane fuel cells enabled by freeze–casting and direct membrane deposition - Hyeon-Seung Jung; Seung Tae Lee; Seung-Hyeon Moon; Chanho Pak; Jae-Hun Kim (Chemical Engineering Journal, 2026)

Comparative analysis of hydrodynamic and reactor design effects on performance in bioreactors - Parth Shah; Satchit Nagpal; Dong Hun Kwak; Jung Ho Kim; Jae Hoon Cho; Jun-Woo Kim; Kosan Roh; Sang Min Park; Joseph Sang-II Kwon (Chemical Engineering Journal, 2026)

Reduction of viability, heat resistance, and biofilm formation and persistence of Bacillus cereus spores in beef stew broth by herb and spice extracts - Gyeong-Jong Kim; Young Hun Jin; Jae-Hyung Mah (Food Research International, 2025)

Bioprinting of cardiac patches with gold-nanowires and tri-culture system for the treatment of myocardial infarction - WonJin Kim; Jung Won Yoon; Woo-Sup Sim; Ye Seul Kim; SooJung Chae; Byungjoon Choi; Hun-Jun Park; Jae Ho Kim; GeunHyung Kim (Chemical Engineering Journal, 2025)

Comparative study of the stability of composite cathodes based on sulfide solid electrolytes for all-solid-state lithium-ion batteries - Jae-Ho Park; Jiwon Jeong; Daseul Han; Jun Tae Kim; Hun-Gi Jung; Woo Young Yoon; Kyung-Wan Nam; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Synergistic improvement of biohydrogen yield from food wastewater using Clostridium puniceum and magnetite-biochar - Jinok Oh; Yebin Han; Gaeun Lim; Shashi Kant Bhatia; Yun-Gon Kim; Sang-Ho Lee; Jae-Seok Kim; Yung-Hun Yang (Bioresource Technology, 2025)

Development of scalable precision fermentation and chemical-grade purification of 5-aminovaleric acid for high-value valorization - Yunhee Jeong; Younghoon Kim; Kyung-An Kim; Yu Jung Sohn; KwangYoung Park; Eunchae Song; Kyungmoon Park; See-Hyoung Park; Yung-Hun Yang; Jong Hyun Choi; Seojin Shin; Wangyun Won; et al. (Chemical Engineering Journal, 2025)

Identification of candidate genes associated with resistance to Heterodera sojae in soybean - Heonil Kang; Jiyong Song; Hyoung-Rai Ko; Jae Eun Jo; Ji-Hun Hwang; Yeon-Ki Kim; Soo-Kwon Park; Gyu Tae Park; Tae-Hwan Jun; Bo-Keun Ha; Zenglu Li; Kyung Do Kim (Theoretical and Applied Genetics, 2025)

Preventive effects of fermented soy protein isolate with Limosilactobacillus fermentum on D-galactose-induced senile osteoporosis in rats via gut microbiome modulation - Jae Yeon Joung; Siyeon Shin; Sae Hun Kim (Food Bioscience, 2025)

Advanced catalytic support materials featuring polymeric short-side chains for PEM water electrolysis anodes - Jae-Hun Kim; Hye Jin Lee; Soo Youn Lee; Min Su Noh; Eun Jeong Shin; Hwi Jong Jung; Yuri Kim; Hee-Young Park; Hee Soo Kim; Jiye Lee; Eunjik Lee; Eunsung Kan; et al. (Chemical Engineering Journal, 2025)

Ionomer-driven selectivity control in natural sunlight-powered CO₂ electrolysis using Ag electrodes in seawater - Sang Youn Chae; Jae Hong Kim; Jung Hun Maeng; Bohyeon Hwang; Gun Sik Yang; Minki Jun; Jin Young Kim; Eun Duck Park (Chemical Engineering Journal, 2025)

Rational design strategy of co-self-assembled monolayers for high-efficiency and stable inverted perovskite solar cells - Haoran Zhou; Jung Jae Do; Young Hun Jung; Hoon Kang; Soyeon Kwon; Gyung Hyun Kim; Yekyung Kim; Tae Hoon Park; Eun Joong Kim; Chang Woo Byun; Jang Hyuk Kwon; Sungyeop Jung; et al. (Chemical Engineering Journal, 2025)

Fundamental modeling of microbial electrosynthesis system using porous electrodes for CO2-to-acetate conversion - Minji Kim; Jiin Yoo; Minsoo Kim; Ji Hun Kim; Yonghyun Lee; Huiwon Lee; Hyoung-il Kim; Jungho Jae; Jung Rae Kim; Sang Hwan Son (Bioresource Technology, 2025)

Inhibitory effects of garlic, cinnamon, and rosemary on viability, heat resistance, and biofilm formation of Bacillus cereus spores in the broth of a fermented soybean paste stew, Cheonggukjang jjigae - Sohyeon Kim; Young Hun Jin; Jae-Hyung Mah (Food Research International, 2025)

Demonstrating the use of absolute pressure sensors for monitoring stack-driven pressure differences in high-rise buildings - Jiajun Jing; Sungmin Yoon; Jaewan Joe; Eui-Jong Kim; Young-Hum Cho; Jae-Hun Jo (Building and Environment, 2025)

Impact of administration routes and dose frequency on the toxicology of SARS-CoV-2 mRNA vaccines in mice model - Jae-Hun Ahn; Jisun Lee; Gahyun Roh; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Kang-Min Han; Ji-Eun Kim; Hyo-Jung Park; Soyeon Yoo; Sung Pil Kwon; Eun-Kyoung Bang; et al. (Archives of Toxicology, 2025)
The increasing use of SARS-CoV-2 mRNA vaccines has raised concerns about their potential toxicological effects, necessitating further investigation to ensure their safety. To address this issue, we aimed to evaluate the toxicological effects of SARS-CoV-2 mRNA vaccine candidates formulated with four different types of lipid nanoparticles in ICR mice, focusing on repeated doses and administration routes. We conducted an extensive analysis in which mice received the mRNA vaccine candidates intramuscularly (50 μg/head) twice at 2-week intervals, followed by necropsy at 2 and 14 dpsi (days post-secondary injection). In addition, we performed a repeated dose toxicity test involving three, four, or five doses and compared the toxicological outcomes between intravenous and intramuscular routes. Our findings revealed that all vaccine candidates significantly induced SARS-CoV-2 spike protein-specific IgG and T cell responses. However, at 2 dpsi, there was a notable temporary decrease in lymphocyte and reticulocyte counts, anemia-related parameters, and significant increases in cardiac damage markers, troponin-I and NT-proBNP. Histopathological analysis revealed severe inflammation and necrosis at the injection site, decreased erythroid cells in bone marrow, cortical atrophy of the thymus, and increased spleen cellularity. While most toxicological changes observed at 2 dpsi had resolved by 14 dpsi, spleen enlargement and injection site damage persisted. Furthermore, repeated doses led to the accumulation of toxicity, and different administration routes resulted in distinct toxicological phenotypes. These findings highlight the potential toxicological risks associated with mRNA vaccines, emphasizing the necessity to carefully consider administration routes and dosage regimens in vaccine safety evaluations, particularly given the presence of bone marrow and immune organ toxicity, which, though eventually reversible, remains a serious concern.

Limosilactobacillus fermentum MF10 promotes hair growth through upregulation of Wnt/β-catenin signaling in C57BL/6 mice - Jae-Young Kim; Sejin Jang; Seokyoung An; Sae Hun Kim (Food Bioscience, 2025)

Symmetric and asymmetric non-fullerene acceptors cooperate synergistically for ternary optoelectronic devices - Minyoung Lim; Xiaoling Ma; Yelim Kang; Min Hun Jee; Soonyong Lee; Sang Young Jeong; Tae Hyuk Kim; Jae Won Shim; Fujun Zhang; Han Young Woo (Chemical Engineering Journal, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Inter-annual changes in transboundary air quality from KORUS-AQ 2016 to SIJAQ 2022 campaign periods and assessment of emission reduction strategies in Northeast Asia - Min-Jun Park; Seung-Hee Baek; Hyo-Jung Lee; Hyun-Young Jo; Cheol-Hee Kim; Jin-Seok Kim; Jung-Hun Woo; Rokjin Park; Jong-Jae Lee; Chang-Keun Song; Jung-Woo Yoo; Lim-Seok Chang; et al. (Environmental Pollution, 2024)

Hydrogen-bonded QSEBS/ZrO2 mixed matrix anion exchange membranes for water electrolyzer - Ji Eun Kim; Young Hwa Yun; Hyeonjung Park; Justin Albers; Gisu Doo; Sechan Lee; Jongsu Seo; Changsoo Lee; MinJoong Kim; Hyun-Seok Cho; Sang-Kyung Kim; Jae Hun Lee; et al. (Fuel, 2024)

Fabrication of granular three-dimensional graphene oxide/UiO-66 adsorbent for high uranium adsorption: Density functional theory and fixed bed column studies - Choe Earn Choong; Yoon-Young Chang; Jae-kyu Yang; Jung Rae Kim; Sang-Eun Oh; Yeomin Yoon; Byong-Hun Jeon; Eun Ha Choi; Min Jang (Journal of Hazardous Materials, 2024)

A new integrated framework to fault detection and diagnosis of air handling unit: Emphasizing the impact of symptoms - Jae Hwan Cha; Jun Kyu Park; Chang Hyeon Chi; Sang Hun Yeon; Chul Ho Kim; Jin Woo Moon; Kwang Ho Lee (Energy and Buildings, 2024)

Enhanced oxidation of parabens in an aqueous solution by air-assisted cold plasma - Hee-Jun Kim; Tae-Hun Lee; Youngpyo Hong; Jae-Cheol Lee; Hyun-Woo Kim (Chemosphere, 2024)

Improvement of 1,3-propanediol production from glycerol using formate as an intermediary metabolite for NADH regeneration in Klebsiella oxytoca - Eun Joo Park; Minsoo Kim; Da Seul Kong; Eunseo Kim; Won Gyeong Park; Jungho Jae; Min Jang; Byong-Hun Jeon; Jung Rae Kim (Biomass and Bioenergy, 2024)

In silico identification and expression analysis of superoxide dismutases in Tenebrio molitor - Ho Am Jang; Hyeonjun Shin; Seo Jin Lee; Sung Min Ku; Jae Hui Kim; Dong Woo Kang; So Yeon Choi; Sang Mok Jung; Hyun Woung Shin; Yong Seok Lee; Yeon Soo Han; Yong Hun Jo (Genes & Genomics, 2024)

Hydrophobicity and membrane distillation performance of glass fiber membranes modified by dip coating of pure PDMS - Minsu Pyo; Sanghyun Jeong; Jae Hun Kim; Min Jung Jeon; Eui-Jong Lee (Journal of Environmental Chemical Engineering, 2024)

A sustainable bioprocessing system leveraging gas fermentation and bipolar membrane electrodialysis system for direct recovery of acetic acid - Mungyu Lee; Jae-Hun Kim; Muhammad Yasin; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2024)

In silico identification and expression analyses of peroxidases in Tenebrio molitor - Ho Am Jang; Sung Min Ku; Jae Hui Kim; Sang Mok Jung; Jongdae Lee; Yong Seok Lee; Yeon Soo Han; Yong Hun Jo (Genes & Genomics, 2024)

Imbalance of sediment transport in a meso-tidal bay: effect of tidal pumping and residual circulation - Su In Kim; Jun Young Seo; Jae-Hun Park; Pyeong Joong Kim; In Gwon Kim; Kyung Man Kim; Ho Kyung Ha (Frontiers in Marine Science, 2024)
In-situ mooring systems with acoustic Doppler current profilers were installed in the western (TM01) and eastern (TM02) parts of Yeosu Bay from September 3 to October 2, 2021, to understand the controlling mechanisms of suspended sediment transport. In the bay, freshwater from the Seomjin River freely exchanges with seawater from the open sea. Over the mooring period, current flows were mainly dominated by ebb tides. Power spectral density analysis of the suspended sediment concentration (SSC) exhibited a quarter-diurnal (6.21 h) frequency at TM01 and a semi-diurnal (12.42 h) frequency at TM02. The results suggested that SSC variations in the western part were driven primarily by local sediment resuspension, while they were influenced predominantly by horizontal advection in the eastern part. Differences in SSC variation at the two stations could be due to the physical properties of the bed sediments (TM01: sandy mud containing shell fragments, TM02: mud). Such current flows and SSC variations over the tidal cycles caused an imbalance of sediment transport. At TM01, the sediment fluxes were dominantly seaward due to tidal pumping (88% of the total) and the discharge of suspended sediments in the surface layer by residual circulation. At TM02, landward sediment fluxes were driven primarily by the residual current (73% of the total). Although the suspended sediment fluxes tended to be compensated and balanced mutually by circulation over the entire period, the suspended sediment fluxes at TM02 were approximately twice higher than those at TM01. This was caused by the difference in SSC asymmetry between flood and ebb at the two stations. The mechanisms controlling the transport of suspended sediment could vary spatially, and the relative contribution of tidal pumping and residual circulation could result in an imbalance of sediment transport.

Estimating three-dimensional current fields in the Yeosu Bay using coastal acoustic tomography system - Yerin Hwang; Eun-Joo Lee; Hajin Song; Byoung-Nam Kim; Ho Kyung Ha; Yohan Choi; Jae-Il Kwon; Jae-Hun Park (Frontiers in Marine Science, 2024)
Observation of current speeds in coastal seas is crucial because it can provide useful information for ship operations, fishing activities, and rapid responses to marine disasters. Coastal acoustic tomography (CAT) is a technology that can continuously monitor environmental changes such as current velocity and water temperature using reciprocal acoustic signals between CAT stations in coastal seas. This technology is different from traditional pointwise or intermittent sectional observations in that it can produce time-varying two- or three-dimensional current fields. The results of previous studies using CAT systems have been limited to reproducing horizontal maps of depth-averaged two-dimensional current fields. Utilizing results from a high-resolution coastal ocean model, this study developed a novel technique for estimating three-dimensional (3-D) current fields by combining the inverse method with an artificial intelligence (AI) model. Following three steps are the procedure for the test of estimating the 3-D current fields. First, utilizing the ray tracing model ‘Bellhop,’ reciprocal travel times among five CAT stations using the coastal ocean model outputs are computed. These five stations correspond to the locations where in-situ CAT systems were established for continuous monitoring of current changes in Yeosu Bay, Korea. Subsequently, the range-averaged currents at the five layers were estimated by incorporating this travel time difference data into an AI model trained using the same coastal ocean model outputs. Finally, the inverse method is applied to each layer to estimate the 3-D current fields. The validation results revealed that the newly developed method performed well in both summer and winter. Time-varying two-layer-like current fields were reasonably produced, occasionally revealing an out-of-phase relationship between the upper and lower layers depending on the tidal phases. This method yielded average root-mean-squared errors of less than 4 cm/s on six simulation paths for acoustic signal propagation. Furthermore, when the same method was applied to in-situ CAT observations, the average correlation coefficient (R) of the along-channel current of each layer was found to be approximately 0.9 or higher. These results suggest that this novel method can be effectively applied to the continuous monitoring of 3-D current fields in coastal seas using a CAT system.

Enhancing polyethylene terephthalate conversion through efficient microwave-assisted deep eutectic solvent-catalyzed glycolysis - Geon-Soo Ha; Md Al Mamunur Rashid; Jeong-Myeong Ha; Chun-Jae Yoo; Byong-Hun Jeon; Keunhong Jeong; Kwang Ho Kim (Chemosphere, 2024)

Integrating experimental and computational approaches for deep eutectic solvent-catalyzed glycolysis of post-consumer polyethylene terephthalate - Geon-Soo Ha; Md Al Mamunur Rashid; Da Hae Oh; Jeong-Myeong Ha; Chun-Jae Yoo; Byong-Hun Jeon; Bonwook Koo; Keunhong Jeong; Kwang Ho Kim (Waste Management, 2024)

Unveiling microplastics with hyperspectral Raman imaging: From macroscale observations to real-world applications - Wooseok Sim; Si Won Song; Subeen Park; Jin Il Jang; Jae Hun Kim; Yeo-Myoung Cho; Hyung Min Kim (Journal of Hazardous Materials, 2024)

Correlation between the particle size of Li1.3Al0.3Ti1.7(PO4)3 solid electrolyte and lithium-ion transport in composite cathodes for all-solid-state lithium-ion batteries - Jae-Ho Park; Mingony Kim; Min-Young Kim; Jiwon Jeong; Hun-Gi Jung; Woo Young Yoon; Kyung Yoon Chung (Chemical Engineering Journal, 2024)

Remote impacts of low-latitude oceanic climate on coastal upwelling in a marginal sea of the Northwestern Pacific - Seongho Lee; Jeong-Yeob Chae; Jae-Hun Park; Young Taeg Kim; Boonsoon Kang; Chang-Woong Shin; Ho Kyung Ha (Regional Studies in Marine Science, 2024)

Rapid and facile preparation of freestanding dense polymer membranes from high-boiling-point solvents for anion exchange membrane water electrolyzers - Du Ru Kang; Gi Hyo Sim; So Youn Lee; Jae Hun Lee; Ki Chul Kim; Jong Hak Kim (Chemical Engineering Journal, 2024)

Screening for Lactic Acid Bacterial Strains as Probiotics Exhibiting Anti-inflammatory and Antioxidative Characteristic Via Immune Modulation in HaCaT Cell - Min Jae Shin; Chul Sang Lee; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2023)

Investigating the Mesh Size Selectivity of Olive Flounder (Paralichthys olivaceus) Gillnets for Fisheries Resource Management in the East Sea - Hyun-Ji Yu; Young Il Seo; Jae-Hyeong Yang; Jeong-Ik Baek; Seong hun Kim (Fishes, 2023)
This study aimed to evaluate the mesh selectivity of gillnets used in olive flounder (Paralichthys olivaceus) fishing by examining the distribution of total length (TL) across various mesh sizes. A marine fishing experiment was conducted at Gajin Harbor in Goseong County, Gangwon Province, employing experimental gear with four different mesh sizes: 90, 105, 135, and 150 mm. Mesh selectivity analysis involved a comparative assessment of selectivity curve methods through normal, log-normal, and bi-normal functions. Among these, the bi-normal function demonstrated the best fit for estimating the mesh selectivity curve within the SELECT model. The critical finding was the net size at which 50% of the minimum landing size (35 cm in TL) of olive flounder was selected, ranging from 108.7 to 121.1 mm. According to the bi-normal function curve, this size was estimated as 114.0 mm. Our findings indicate that using a mesh size larger than the theoretically estimated size in mesh selectivity analysis can further decrease the catch of immature individuals. These findings provide essential data for devising strategies to efficiently utilize and manage olive flounder resources.

Biofloc Application Using Aquaponics and Vertical Aquaculture Technology in Aquaculture: Review - Young-Bin Yu; Jae-Ho Choi; Ju-Hyeong Lee; A-Hyun Jo; Sung Won Han; Song-Hun Han; Hee Jae Choi; Cheol Young Choi; Ju-Chan Kang; EunYoung Min; Jun-Hwan Kim (Fishes, 2023)
Some aspects of traditional aquaculture have negative impacts on the aquatic environment, leading to pollution and disease outbreaks in farmed organisms. Biofloc technology (BFT) is a closed aquaculture system that utilizes specific microbial communities to remove ammonia emitted from aquaculture organisms or adds carbon to the aquaculture system to improve water quality. BFT has benefits, such as increasing production and improving water quality, and reducing disease spread and pollution, without the need for water exchange. However, there are disadvantages, such as rapid changes in water quality due to accumulation of dissolved nutrients and total suspended soils (TSS) and the requirement for expensive aeration equipment to maintain dissolved oxygen. BFT can be enhanced in value and efficiency by combining it with other aquaculture technologies, such as aquaponics and vertical aquaculture to overcome the disadvantages. The integration of biofloc with technologies from the fourth industrial revolution holds potential for further development, while aquaponics and vertical farming can eliminate geographical limitations and accelerate the urbanization of aquaculture. The integration of aquaponics and vertical aquaculture with BFT has potential for development, accelerating the urbanization of aquaculture and removing geographic limitations.

Biogenic amine reduction by vasoactive amine-degrading Bacillus licheniformis CH7P22 in Enterococcus faecium-contaminated Cheonggukjang, Korean fermented soybean paste - Dabin Kim; Young Hun Jin; Jae-Hyung Mah (Food Control, 2023)

Extremely high selective Si1−xGex-film wet etchant generating highly dissolved oxygen via peracetic acid oxidant for lateral gate-all-around FETs with a logic node of less than 3-nm - Seung-Jae Lee; Ji-Eun Lee; Chang-Jin Lee; Ji-Hoon Kim; Ji-Hun Kim; Min-Won Kim; Ji-Ho Choi; Ui-Hyun Jeong; Jea-Gun Park (Chemical Engineering Journal, 2023)

Review of technology and materials for the development of cultured meat - Da Young Lee; Seung Yun Lee; Jae Won Jung; Jae Hyun Kim; Dong Hun Oh; Hyun Woo Kim; Ji Hyeop Kang; Jung Seok Choi; Gap-Don Kim; Seon-Tea Joo; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2023)

Real-time morphological detection of label-free submicron-sized plastics using flow-channeled differential interference contrast microscopy - Jiyun Han; Subeen Park; Mingizem Gashaw Seid; Byeongho Park; Soo Hyun Lee; Hyung Min Kim; Changha Lee; Jaesang Lee; Jae Hun Kim; Seok Won Hong (Journal of Hazardous Materials, 2023)

Efficient chemo-catalytic transformation of spent coffee grounds into lactic acid using erbium triflate - Geon-Soo Ha; Ho Seung Song; Da Hae Oh; Mark Mba-Wright; Jeong-Myeong Ha; Chun-Jae Yoo; Jae-Wook Choi; Chang Soo Kim; Byong-Hun Jeon; Hanseob Jeong; Kwang Ho Kim (Journal of Environmental Chemical Engineering, 2023)

Antioxidant-Coated multifunctional whitlockite scaffold for the treatment of Steroid-Induced osteonecrosis of the femoral head - Jung Hun Kim; QuanZhe Liu; Uk-Jae Lee; Arun Kumar Rajendran; MinJoon Cho; Sivashanmugam Amirthalingam; Tae Hoon Kang; Beom Seok Kim; Gyeong-Guk Park; Byung-Gee Kim; Jae Hyup Lee; Nathaniel S. Hwang (Chemical Engineering Journal, 2023)

A versatile hybrid catalyst platform of Na/ZnFe2O4 and zeolite for selective hydrocarbon production from CO2 hydrogenation - Eun Cheol Ra; Sejin Jang; Dong Gun Oh; Ju Hyeong Lee; Hyo Eun Kim; Eun Hyup Kim; Kwang Young Kim; Min Hee Lee; Kwang Hyun Kim; Ja Hun Kwak; Jae Sung Lee (Chemical Engineering Journal, 2023)

Wintertime sea surface temperature variability modulated by Arctic Oscillation in the northwestern part of the East/Japan Sea and its relationship with marine heatwaves - Se-Yong Song; Yoo-Jun Kim; Eun-Joo Lee; Sang-Wook Yeh; Jae-Hun Park; Young-Gyu Park (Frontiers in Marine Science, 2023)
The northwestern part of the East/Japan Sea (EJS) is a region with large sea surface temperature (SST) variability and is known as a hotspot of marine heatwaves (MHW) stress for marine environments that peaked in boreal winter (January-February-March). This could have profound impacts on the marine ecosystems over the EJS. Here, we used a set of high-resolution satellite and reanalysis products to systematically analyze the spatiotemporal SST variations and examine their linkage to a large-scale mode of climate variability, such as the Arctic Oscillation (AO). The results show that AO-related wind forcing modulates the SST variability over the EJS via the oceanic dynamic adjustment processes. In particular, the abnormally warm SSTs in the northwestern part of the EJS are driven by the anomalous anticyclonic eddy-like circulation and Ekman downwelling during a positive AO phase. This physical linkage between a positive AO and the abnormally warm SST could be conducive to MHW occurrences in the EJS as in the extremely positive AO event during the winter of 2020. These results have implications that the MHW occurrences in the EJS could be amplified by natural climate variability along with long-term SST warming.

Seasonal Variability of the Deep Western Boundary Current in the Philippine Sea - Hajin Song; Xiao-Hua Zhu; Ze-Nan Zhu; Jeong-Yeob Chae; Chanhyung Jeon; Dong-Guk Kim; Hong-Sik Min; Jae-Hak Lee; Jae-Hun Park (Journal of Marine Science and Engineering, 2023)
The deep western boundary current (DWBC) in the Philippine Sea has been expected to play a crucial role in transporting lower circumpolar deep water and to contribute to regional and global climate regulation. Two-year-long near-bottom current measurements reveal a southward-flowing DWBC with a mean velocity of 5 cm/s and seasonal variations—weaker in summer and stronger in winter. Seasonal variability in the DWBC is hypothesized to be induced by changes in the North Equatorial Current bifurcation latitude (NECBL) and upper pycnocline depth through potential vorticity conservation. Data-assimilated reanalysis model (GLORYS12V1) outputs, which reproduce the seasonal variability of DWBC similarly to the observation, are used for further analysis. During the seasonal period, the NECBL displays significant coherence (>0.9) with the first-mode empirical orthogonal function principal component of the simulated along-slope DWBC. The upper pycnocline depth, varying seasonally within a range of approximately 27 m, induces seasonal variability in a deep anticyclonic eddy trapped by topography. In summer, the intensified deep anticyclonic eddy obstructs the adjacent southward-flowing DWBC, weakening its strength, whereas in winter, the southward flow of the DWBC is enhanced due to the weakening of the deep anticyclonic eddy.

Multiscale strategy to predict the fracture toughness and crack extension behavior of ozone-functionalized carbon nanotube/epoxy nanocomposites - Haolin Wang; Jihun Lee; Jae Hun Kim; Hyunseong Shin (Chemical Engineering Journal, 2023)

Recycling of minerals with acetate separation in biological syngas fermentation with an electrodialysis system - Jae-Hun Kim; Mungyu Lee; Hoyoung Jeong; Songju Ko; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2023)

Bone Regeneration with 3D-Printed Hybrid Bone Scaffolds in a Canine Radial Bone Defect Model - Yoon Jae Lee; Yeon Hee Ryu; Su Jin Lee; Suk-Ho Moon; Ki Joo Kim; Byeong Ju Jin; Kyoung-Don Lee; Jung Kyu Park; Jin Woo Lee; Seung-Jae Lee; Hun-Jin Jeong; Jong Won Rhie (Tissue Engineering and Regenerative Medicine, 2022)

Reconstruction of long-term sea-level data gaps of tide gauge records using a neural network operator - Eun-Joo Lee; Kiduk Kim; Jae-Hun Park (Frontiers in Marine Science, 2022)
The coastal sea level is an important factor in understanding and clarifying the physical processes in coastal seas. However, missing values and outliers of the sea level that occur for various reasons often disrupt the continuity of its time series. General-purpose time-series analysis and prediction methods are not tolerant of missing values, which is why researchers have attempted to fill these gaps. The disadvantage of conventional time-series reconstruction techniques is the low accuracy when missed sea-level records are longer than the timescales of coastal processes. To solve this problem, we used an artificial neural network, which is a novel tool for creating multivariate and nonlinear regression equations. The trained neural network weight set was designed to enable long-term reconstruction of sea level by acting as a one-step prediction operator. In addition, a data assimilation technique was developed and adapted to ensure seamless continuity between predicted and observed sea-level records. The application of our newly developed method to 3-day gaps of seal level records at 16 tide gauge stations around the Korean peninsula confirms that it can successfully reconstruct missing values with root-mean-squared errors of 0.5–1.1 cm on average.

Weakening of the Kuroshio Upstream by Cyclonic Cold Eddies Enhanced by the Consecutive Passages of Typhoons Danas, Wipha, and Francisco (2013) - Chanhyung Jeon; D. Randolph Watts; Hong Sik Min; Dong Guk Kim; Sok Kuh Kang; Il-Ju Moon; Jae-Hun Park (Frontiers in Marine Science, 2022)
An array of five pressure-recording inverted echo sounder (PIES) moorings spanning a distance of 420 km around the subtropical countercurrent and North Equatorial Current regions of the western Pacific detected extraordinary sea level drops from November to December 2013. In October 2013, three typhoons, namely, Danas, Wipha, and Francisco, consecutively passed east of the PIES sites, which significantly strengthened pre-existing cyclonic cold eddies to create the observed sea level drops. The typhoon-strengthened cold eddies propagated westward over approximately 1000 km for approximately 4 months and eventually met the Kuroshio offshore Taiwan. The approaching eddies interacted with the Kuroshio upstream for ~3 months and reduced the Kuroshio intensity by up to 24% in February–May 2014, the lowest record for the last 26 years of satellite measurements. Our results can provide a new mechanism linking typhoon-to-eddy-to-Kuroshio variability through oceanic processes.

Identification of novel candidate genes implicated in odontogenic potential in the developing mouse tooth germ using transcriptome analysis - Yeo-Kyeong Shin; Seongmin Cheon; Sung-Duk Kim; Jung-Sun Moon; Jae-Young Kim; Sun-Hun Kim; Chungoo Park; Min-Seok Kim (Genes & Genomics, 2021)

Novel Method for the Estimation of Vertical Temperature Profiles Using a Coastal Acoustic Tomography System - Yeongbin Park; Chanhyung Jeon; Hajin Song; Youngseok Choi; Jeong-Yeob Chae; Eun-Joo Lee; Jin Sung Kim; Jae-Hun Park (Frontiers in Marine Science, 2021)
Systems based on remote sensing technology, which use reciprocal acoustic signals to continuously monitor changes in the coastal oceanic environment, are referred to as coastal acoustic tomography (CAT) systems. These systems have been applied in regions in which heavy ship traffics, fishing and marine aquaculture activities make it difficult to establish in situ oceanic sensor moorings. Conventionally, CAT measurements were used to successfully produce horizontal maps of the depth-averaged current velocity and temperature in these coastal regions without attempting to produce a vertical temperature profile. This prompted us to propose a new method for vertical temperature profile estimation (VTPE) from CAT data using the available sea surface temperature (SST), near-bottom temperature (NBT), and water depth. The VTPE method was validated using data-assimilated and tide-included high-resolution ocean model outputs, including tide data, by comparing the estimated and simulated temperatures. Measurements were performed in the southern coastal region of Korea, where two CAT stations were moored to establish a continuous coastal ocean monitoring system. The validation results revealed that the algorithm performed well across all seasons. Sensitivity tests of the VTPE method with reasonable realistic random errors in the SST, NBT, and acoustic travel time measurements demonstrate that the method is applicable to CAT observation data because the monthly mean root-mean-squared difference (RMSD) for the vertical profiles for February, May, August, and November were 0.23, 0.30, 0.50, and 0.24°C, respectively. The VTPE method was applied to the CAT observation datasets acquired in February and August. The transceivers at the CAT stations were at depths 11 and 6 m on average. The RMSD between the estimated and observed temperatures in the middle layer (∼3 m depth) between two stations in February and August were 0.08 and 0.60°C, respectively, the accuracy of which is sufficient in largely time-varying coastal environments. We provide a novel method for continuous coastal subsurface environmental monitoring without interrupting maritime traffic, fishing, and marine aquaculture activities.

Variation of Semidiurnal Internal Tides along the Southeastern Coast of Korea Induced by Typhoons - Jeong-Yeob Chae; Chanhyung Jeon; Pyeongjoong Kim; Naoki Hirose; Ahyoung Ku; Jae-Hun Park (Journal of Marine Science and Engineering, 2021)
Typhoon-induced strong winds can dramatically change the oceanic environment, occasionally resulting in sudden stratification changes. In July 2015, two consecutive typhoons, Chanhom and Nangka, passed over the Yellow and East/Japan Seas within a week. Remarkable temperature variations were observed near the southeastern coast of Korea, caused by typhoon-induced upwelling and downwelling events, which altered the energy of semidiurnal internal tides. During the typhoon-induced downwelling event, the energy of semidiurnal internal tides near the southeastern coast of Korea varied independently from the barotropic tidal forcing. Data-assimilated numerical simulation results reveal that the pycnocline, which is typically tilted toward the coast, enables the semidiurnal internal tidal energy to propagate toward shallow regions after being generated off the coast. Meanwhile, the downwelling event deepens the pycnocline near the coast and reflects and concentrates the semidiurnal internal tide energy near the bottom off the coast. A simple mechanism using the ratio between the wave characteristic slope and the bottom slope is proposed to explain the observed variations of semidiurnal internal tide energy near the coast. This paper demonstrates a case study showing that typhoon passage can modify the energetics of internal tides, which has the potential to cause unusual short-term coastal environmental changes.

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Protective effect of Lactobacillus casei HY2782 against particulate matter toxicity in human intestinal CCD-18Co cells and Caenorhabditis elegans - Joo Yeon Kim; So Young Lee; Seung-Hee Jung; Mi Ri Kim; Il-Dong Choi; Jung-Lyoul Lee; Jae-Hun Sim; Cheol-Ho Pan; Kyungsu Kang (Biotechnology Letters, 2020)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Thermoresponsive and Biodegradable Amphiphilic Block Copolymers with Pendant Functional Groups - Bo Keun Lee; Jung Hyun Noh; Ji Hoon Park; Seung Hun Park; Jae Ho Kim; Se Heang Oh; Moon Suk Kim (Tissue Engineering and Regenerative Medicine, 2018)

Comparison of Measurements from Pressure-recording Inverted Echo Sounders and Satellite Altimetry in the North Equatorial Current Region of the Western Pacific - Chanhyung Jeon; Jae-Hun Park; Dong Guk Kim; Eung Kim; Dongchull Jeon (Ocean Science Journal, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Effect of Drug Carrier Melting Points on Drug Release of Dexamethasone-Loaded Microspheres - Ji Hoon Park; Doo Yeon Kwon; Ji Yeon Heo; Seung Hun Park; Joon Yeong Park; Bong Lee; Jae Ho Kim; Moon Suk Kim (Tissue Engineering and Regenerative Medicine, 2017)

Novel reassortant clade 2.3.4.4 avian influenza A (H5N8) virus in a grey heron in South Korea in 2017 - Chanjin Woo; Jung-Hoon Kwon; Dong-Hun Lee; Youngsik Kim; Kwanghee Lee; Seong-Deok Jo; Ki dong Son; Jae-Ku Oem; Seung-Jun Wang; Yongkwan Kim; Jeonghwa Shin; Chang-Seon Song; et al. (Archives of Virology, 2017)

Simulations of the Population Dynamics of Jellyfish Polyps Living on Artificial Substrates in Coastal Areas - Hong Sung Jin; Dongyeob Han; Jung-Hun Kim; Hyun-Jae Shin; Yang Ho Yoon; Chang-hoon Han (Thalassas: An International Journal of Marine Sciences, 2017)

Cardiac inotropy, lusitropy, and Ca2+ handling with major metabolic substrates in rat heart - Zai Hao Zhao; Jae Boum Youm; Yue Wang; Jeong Hoon Lee; Jae Hwi Sung; Joon-Chul Kim; Sun Hee Woo; Chae Hun Leem; Sung Joon Kim; Lan Cui; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2016)

Use of nonhuman primates for the development of bioengineered female reproductive organs - Jun-Won Yun; Yoon Young Kim; Jae Hun Ahn; Byeong-Cheol Kang; Seung-Yup Ku (Tissue Engineering and Regenerative Medicine, 2016)

Predicting chlorophyll- a using Landsat 8 OLI sensor data and the non-linear RANSAC method – a case study of Nakdong River, South Korea - Hyeong Hun Kim; Byoung Chul Ko; Jae Yeal Nam (International Journal of Remote Sensing, 2016)

Behavior, PET and histology in novel regimen of MPTP marmoset model of Parkinson’s disease for long-term stem cell therapy - Jun-Won Yun; Jae-Bum Ahn; Euna Kwon; Jae Hun Ahn; Hyung Woo Park; Hwon Heo; Jin-Sung Park; Hyeonjin Kim; Sun Ha Paek; Byeong-Cheol Kang (Tissue Engineering and Regenerative Medicine, 2016)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Comparison of the toxicity of aluminum oxide nanorods with different aspect ratio - Eun-Jung Park; Gwang-Hee Lee; Jae-hun Shim; Myung-Haing Cho; Byoung-Seok Lee; Yong-Bum Kim; Jae-Ho Kim; Younghun Kim; Dong-Wan Kim (Archives of Toxicology, 2015)

Effects of reduced vertical mixing under sea ice on Atlantic meridional overturning circulation (AMOC) in a global ice-ocean model - Sang Yeob Kim; Ho Jin Lee; Jae-Hun Park; Young Ho Kim (Ocean Science Journal, 2015)

Development of the Operational Oceanographic System of Korea - Kwang-Soon Park; Ki-Young Heo; Kicheon Jun; Jae-Il Kwon; Jinah Kim; Jin-Yong Choi; Kyoung-Ho Cho; Byoung-Ju Choi; Seung-Nam Seo; Young Ho Kim; Sung-Dae Kim; Chan-Su Yang; et al. (Ocean Science Journal, 2015)

Prognostic value of hepatoma-derived growth factor-related protein 3 (HRP-3) methylation in non-small cell lung cancer - Young Hun Kim; Won Kee Lee; Jae Yong Park; Dong Sun Kim (Genes & Genomics, 2015)

Serology and clinical relevance of Corynebacterium pseudotuberculosis in native Korean goats (Capra hircus coreanae) - Byeong Yeal Jung; Seung-Hun Lee; Ha-Young Kim; Jae-Won Byun; Dong-Ho Shin; Daekeun Kim; Dongmi Kwak (Tropical Animal Health and Production, 2015)

Genetic characterization of porcine epidemic diarrhea virus in Korea from 1998 to 2013 - Seong-Hee Kim; Jung-Min Lee; Jongsun Jung; In-Joong Kim; Bang-Hun Hyun; Hyun-Il Kim; Choi-Kyu Park; Jae-Ku Oem; Yeon-Hee Kim; Myoung-Heon Lee; Kyoung-Ki Lee (Archives of Virology, 2015)

Deinococcus radioresistens sp. nov., a UV and gamma radiation-resistant bacterium isolated from mountain soil - Sathiyaraj Srinivasan; Jae-Jin Lee; Sang-Yong Lim; Min-Ho Joe; Seong-Hun Im; Myung Kyum Kim (Antonie van Leeuwenhoek, 2015)

A comparison of the effects of repetitive transcranial magnetic stimulation (rTMS) by number of stimulation sessions on hemispatial neglect in chronic stroke patients - Yong Kyun Kim; Jae Hwan Jung; Sung Hun Shin (Experimental Brain Research, 2015)

Polycyclic aromatic hydrocarbons exposure in residents living near a cement factory with kilns - YongMin Cho; Geun-Bae Kim; Yong-Sung Cho; Min Seok Choi; Seung-Hun Ryu; Seung Hyun Choi; Young-Koo Park; Jae Wook Choi (International Archives of Occupational and Environmental Health, 2014)

Assessment of natural and calcined starfish for the amelioration of acidic soil - Deok Hyun Moon; Jae E. Yang; Kyung Hoon Cheong; Agamemnon Koutsospyros; Jeong-Hun Park; Kyoung Jae Lim; Sung Chul Kim; Rog-Young Kim; Yong Sik Ok (Environmental Science and Pollution Research, 2014)

Genetic structure and variability of the working dog inferred from microsatellite marker analysis - Yun-Jeong Kwon; Bong-Hwan Choi; Jungwoo Eo; Choongrak Kim; Yi-Deun Jung; Ja-Rang Lee; Yuri Choi; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Dae-Soo Kim; Jae-Won Huh; et al. (Genes & Genomics, 2014)

CoCl2 induces apoptosis through the mitochondria- and death receptor-mediated pathway in the mouse embryonic stem cells - Jin-Ha Lee; Seong-Ho Choi; Min-Woo Baek; Mi-Hwa Kim; Heong-Jun Kim; Sun-Hun Kim; Sang-Jin Oh; Hong-Ju Park; Won-Jae Kim; Ji-Yeon Jung (Molecular and Cellular Biochemistry, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Variability of the Dokdo Abyssal Current observed in the Ulleung Interplain Gap of the East/Japan Sea - Yun-Bae Kim; Kyung-Il Chang; Jae-Hun Park; Jong Jin Park (Acta Oceanologica Sinica, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

Effects of substrate concentrations on performance of serially connected microbial fuel cells (MFCs) operated in a continuous mode - Anup Gurung; Jungrae Kim; Sokhee Jung; Byong-Hun Jeon; Jae E. Yang; Sang-Eun Oh (Biotechnology Letters, 2012)

mRNA sequence analysis and quantitative expression of the ADAMTS4 gene in the thoroughbred horse - Jae-Woo Moon; Kung Ahn; Jin-Han Bae; Gyu-Hwi Nam; Byung-Wook Cho; Kyung-Do Park; Hak-Kyo Lee; Young-Mok Yang; Tae-Hun Kim; Hwan-Hoo Seong; Kyudong Han; Heui-Soo Kim (Genes & Genomics, 2012)

Identification and characterization of transposable element-mediated chimeric transcripts from porcine Refseq and EST databases - Hong-Seok Ha; Jae-Woo Moon; Jeong-An Gim; Yi-Deun Jung; Kung Ahn; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

In vitro CpG methylation and garcinol reduce PERV LTR promoter activity - Hong-Seok Ha; Young-Choon Lee; Sang-Je Park; Yi-Deun Jung; Kung Ahn; Jae-Woo Moon; Kyudong Han; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

mRNA-centric semantic modeling for finding molecular signature of trace chemical in human blood - Ga-Hee Shin; Yeon-Kyung Kang; Seung-Hun Lee; Seung Jun Kim; Seung Yong Hwang; Suk-Woo Nam; Jae-Chun Ryu; Byeong-Chul Kang (Molecular & Cellular Toxicology, 2012)

Anti-inflammatory effect of sweetfish-derived protein and its enzymatic hydrolysate on LPS-induced RAW264.7 cells via inhibition of NF-κB transcription - Nak-Yun Sung; Pil-Moon Jung; Minchul Yoon; Jeong-Soo Kim; Jong-il Choi; Hye Gwang Jeong; Ju-Woon Lee; Jae-Hun Kim (Fisheries Science, 2012)

Oxidized phosphatidylcholine induces migration of bone marrow-derived mesenchymal stem cells through Krüppel-like factor 4-dependent mechanism - Sang Hun Shin; Hae Young Song; Min Young Kim; Eun Kyung Do; Jung Sub Lee; Jae Ho Kim (Molecular and Cellular Biochemistry, 2011)

Biological safety and B cells activation effects of Zanthoxylum schinifolium - Dae-Hun Park; Yong-Il Park; Yong-Chun Li; Hong De Xu; Jong-Hwa Lee; Young-Jin Kim; Soon-Ae Jang; Sung Jin Park; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; Min-Jae Lee (Molecular & Cellular Toxicology, 2011)

Stability of Fe- and Mn-(oxyhydr)oxides in Common Soil Dispersion Solutions - Phung N. Manh; Moonis Ali Khan; Byong-Hun Jeon; Jae Gon Kim; Giehyeon Lee (Water, Air, & Soil Pollution, 2011)

Abiotic subsurface behaviors of As(V) with Fe(II) - Sang-Hun Lee; Woosik Jung; Byong-Hun Jeon; Jae-Young Choi; Sunjoon Kim (Environmental Geochemistry and Health, 2011)

Molecular epizootiology of infectious bursal disease (IBD) in Korea - Woo-Jin Jeon; Kang-Seuk Choi; Dong-Woo Lee; Eun-Kyoung Lee; Sang-Ho Cha; Sun-Hee Cho; Jun-Hun Kwon; Yeo-sung Yoon; Sun-Joong Kim; Jae-Hong Kim; Hyuk-Joon Kwon (Virus Genes, 2009)

Detection of low-abundant novel transcripts in mouse hematopoietic stem cells - Hyeng-Soo Kim; Junmo Hwang; Young-Hun Kim; Seonggon Kim; Jae-Woong Lee; Hyung-Sik Kang; Kil Soo Kim; Ji-Hong Ha; Jin Woong Chung; Kyu-Tae Chang; Zae Young Ryoo; Sanggyu Lee (Molecular Genetics and Genomics, 2009)

A volumetric study of the corpus callosum in 20s and 40s Korean people - Beob-Yi Lee; Jin-Hun Sohn; Mi-Hyun Choi; Su-Jeong Lee; Hyo-Seong Kim; Jae-Woong Yang; Jin-Seung Choi; Hyung-Sik Kim; Jeong-Han Yi; Gye-Rae Tack; Soon-Cheol Chung (Brain Structure and Function, 2009)

Vertical structure of low-frequency currents in the southwestern East Sea (Sea of Japan) - Yun-Bae Kim; Kyung-Il Chang; Kuh Kim; Jae-Hun Park; Jae-Hak Lee (Journal of Oceanography, 2009)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Overexpression of OgPAE1 from wild rice confers fungal resistance against Botrytis cinerea - Eun Hee Jeon; Eun Sook Chung; Jung Hun Pak; Jae Sung Nam; Sung Ki Cho; Sang Hyun Shin; Doh Hoon Kim; Gyung Tae Kim; Jai Heon Lee; Kyung Ho Kang; Young Soo Chung (Journal of Plant Research, 2008)

Beneficial effects of cardiac rehabilitation and exercise after percutaneous coronary intervention on hsCRP and inflammatory cytokines in CAD patients - Young-Joo Kim; Young-Oh Shin; Jun-Sang Bae; Jeong-Beom Lee; Joo-Hyun Ham; Youn-Jung Son; Jung-Kyu Kim; Chul Kim; Byoung-Kwon Lee; Jae-Keun Oh; Timothy Othman; Young-Ki Min; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Analysis of metabolite profile data using batch-learning self-organizing maps - Jae Kwang Kim; Myoung Rae Cho; Hyung Jin Baek; Tae Hun Ryu; Chang Yeon Yu; Myong Jo Kim; Eiichiro Fukusaki; Akio Kobayashi (Journal of Plant Biology, 2007)

A Polymeric Nanoparticle Consisting of mPEG-PLA-Toco and PLMA-COONa as a Drug Carrier: Improvements in Cellular Uptake and Biodistribution - Yilwoong Yi; Jae Hong Kim; Hye-Won Kang; Hun Seung Oh; Sung Wan Kim; Min Hyo Seo (Pharmaceutical Research, 2005)

Variation of Species Composition of Benthic Algae and Whitening in the Coast of Dokdo Island during Summer - Mi-Gyeong Kim; Jae-Gi Sin; Jae-Hun Cha (Algae, 2004)

Phylogenetic Relationship of Microcystis (Cyanophyceae) Based on Partial 16S rRNA Gene Sequences in Korea - Jong-In Kim; Jong-Hun Lim; Jae-Wan Lee; Hae-Bok Lee (Algae, 2002)